PERAN BUMDes DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT PERDESAAN (STUDI KASUS DESA RIA BAO KECAMATAN NAGAWUTUNG KABUPATEN LEMBATA) - Sengaji, Roli Oktofianus Puru; Rozari,, Petrus E. de (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 7 (2024): Vol.13.No.7. JULI 2024 [452-544]DO - 10.24843/EEP.2024.v13.i07.p05, 2024)
BUMDes is one of the village government programs to improve the economy of rural communities. Research purposes; (1) knowing the economic potential that exists in Ria Bao Village, (2) knowing the management of BUMDes in Ria Bao Village, (3) knowing the role of BUMDes in empowering the community to improve the economy in Ria Bao Village. The researcher used descriptive qualitative methods with a case study approach. Data collection techniques through observation, interviews and documentation. The research results shows that the potential of the village managed by BUMDes Nogo Gunu, namely agriculture, plantations, animal husbandry and seaweed cultivation through 3 business units, namely savings and loans, joint marketing and animal husbandry, can improve the economy of the community in Ria Bao Village. The obstacles in BUMDes Nogo Gunu management; There are still many people who have not taken the advantage of BUMDes existence, there is no training for BUMDes management. To solve this problem, the BUMDes management continue to carry out the socialization to the community, rent the BUMDes buildings as well as recommendation to provide the training management. Keywords: Role of BUMDes, Improving the Economy